Squamous cell carcinoma arising in an epidermal inclusion cyst. Issue 5 (15th September 2022) - Alkul, Suzanne; Nguyen, Christopher N.; Ramani, Nisha S.; Alkul, Mahmud; Orengo, Ida; Shimizu, Ikue; Krishnan, Bhuvaneswari
Abstract: Squamous cell carcinoma (SCC) arising from an epidermal inclusion cyst (EIC) is uncommon. We present a case of a 70-year-old man with a scalp nodule with persistent discharge that was resected based on the clinical impression of an EIC. Histopathologic exam showed an infundibular EIC with an epidermal type of squamous epithelium; however, some of the cyst lining and lumen was replaced by squamous proliferation with malignant features. There are 56 cases of SCC arising in EICs reported in the English literature. Though suspected EICs are commonly benign, a thorough pathologic evaluation is required to rule out malignancy.